4-[1-(Substituted aryl/alkyl carbonyl)-benzoimidazol-2-yl]-benzenesulfonic acids: Synthesis, antimicrobial activity, QSAR studies, and antiviral evaluation - Yadav, Snehlata (Eur J Med Chem, 2010)
A series of 4-[1-(substituted aryl/alkyl carbonyl)-benzoimidazol-2-yl]-benzene sulphonic acids (1-20) was synthesized and evaluated, in vitro, for their antimicrobial activity and the results indicated that compounds 4-[1-(4-Nitrobenzoyl)-1H-benzoimidazol-2-yl]-benzenesulfonic acid (9) and 4-(1-octadec-9-enoyl-1H-benzoimidazol-2-yl)-benzenesulfonic acid (18) were found to be the most active ones. QSAR investigations indicated that the multi-target QSAR model was effective in describing the antimicrobial activity over the one-target QSAR models. Further the mt-QSAR model indicated the importance of the topological parameter, Balaban index (J) followed by the electronic parameter, LUMO and topological parameter, valence second order molecular connectivity index ((2)χ(v)) in describing the antimicrobial activity of synthesized compounds (1-20).